Carbon Dioxide and Methane Release Following Abrupt Thaw of Pleistocene Permafrost Deposits in Arctic Siberia. Issue 11 (1st November 2021) - Knoblauch, Christian; Beer, Christian; Schuett, Alexander; Sauerland, Lewis; Liebner, Susanne; Steinhof, Axel; Rethemeyer, Janet; Grigoriev, Mikhail N.; Faguet, Alexey; Pfeiffer, Eva‐Maria
Abstract: The decomposition of thawing permafrost organic matter (OM) to the greenhouse gases (GHG) carbon dioxide (CO2 ) and methane forms a positive feedback to global climate change. Data on in situ GHG fluxes from thawing permafrost OM are scarce and OM degradability is largely unknown, causing high uncertainties in the permafrost‐carbon climate feedback. We combined in situ CO2 and methane flux measurements at an abrupt permafrost thaw feature with laboratory incubations and dynamic modeling to quantify annual CO2 release from thawing permafrost OM, estimate its in situ degradability and evaluate the explanatory power of incubation experiments. In July 2016 and 2019, CO2 fluxes ranged between 0.24 and 2.6 g CO2 ‐C m −2 d −1 . Methane fluxes were low, which coincided with the absence of active methanogens in the Pleistocene permafrost. CO2 fluxes were lower three years after initial thaw after normalizing these fluxes to thawed carbon, indicating the depletion of labile carbon. Higher CO2 fluxes from thawing Pleistocene permafrost than from Holocene permafrost indicate OM preservation for millennia and give evidence that microbial activity in the permafrost was not substantial. Short‐term incubations overestimated in situ CO2 fluxes but underestimated methane fluxes. Two independent models simulated median annual CO2 fluxes of 160 and 184 g CO2 ‐C m −2 from the thaw slump, which include 25%–31% CO2 emissions during winter. Annual CO2 fluxes represent 0.8% of the carbon pool thawed in the surface soil. Our results demonstrate the potential of abrupt thaw processes to transform the tundra from carbon neutral into a substantial GHG source. Plain Language Summary: Thawing of permanently frozen soils (permafrost) in the northern hemisphere forms a threat to global climate since these soils contain large amounts of frozen organic carbon, which might be decomposed to the greenhouse gases (GHGs) carbon dioxide (CO2 ) and methane upon thaw. How fast these GHGs are produced is largely unknown, since field observations of greenhouse gas fluxes from thawing permafrost are too sparse. Consequently, simulations on the effect of thawing permafrost soils on future climate are highly uncertain. We measured CO2 and methane fluxes from soils affected by abrupt permafrost thaw in Siberia during two summer seasons. We used these field observations and long‐term incubation data to calibrate two models that simulate the CO2 release over a whole year. We found that greenhouse gas fluxes were dominated by CO2 and that the minor importance of methane was due to the absence of methane producing microorganisms in the Pleistocene permafrost. The CO2 release in the first year accounted for 0.8% of thawed permafrost carbon but decomposition rates decreased after the depletion of the rapidly decomposable organic matter. Abrupt permafrost thaw turned the tundra into a substantial source of CO2, of which 25%–31% was released in the non‐growing season. Key Points: Abrupt permafrost thaw turned the tundra into a substantial annual source of CO2 of which 25%–31% were released in the non‐growing season About 0.8% of thawed permafrost carbon was decomposed to CO2 in one year but decomposition rates declined after the loss of labile carbon Methane contributed a minor fraction to total greenhouse gas fluxes also because of a low methanogen abundance in Pleistocene permafrost